2006
DOI: 10.1249/01.mss.0000210197.02576.da
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Reduces Time to Exhaustion and Insulin Response to a Graded Exercise Test

Abstract: It can be concluded that, contrary to the hypothesized improvement in treadmill time following L-citrulline ingestion, there is a reduction in treadmill time following L-citrulline ingestion over the 24 h prior to testing. The normal response of increased plasma insulin following high-intensity exercise is also not present in the L-citrulline condition, indicating that L-citrulline ingestion may reduce nitric oxide-mediated pancreatic insulin secretion or increased insulin clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 24 publications
1
88
3
1
Order By: Relevance
“…These findings differ from previous research demonstrating that acute Cit supplementation lowers plasma [NOx] and compromises exercise tolerance (26) but are consistent with studies showing that short-term (15 days) supplementation with L-citrulline malate can positively affect skeletal muscle power output and metabolic responses (7). These findings are important, since they suggest that Cit might be responsible for the positive effects previously reported following L-citrulline malate supplementation and offer new insights into the mechanisms by which Cit supplementation might be ergogenic.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings differ from previous research demonstrating that acute Cit supplementation lowers plasma [NOx] and compromises exercise tolerance (26) but are consistent with studies showing that short-term (15 days) supplementation with L-citrulline malate can positively affect skeletal muscle power output and metabolic responses (7). These findings are important, since they suggest that Cit might be responsible for the positive effects previously reported following L-citrulline malate supplementation and offer new insights into the mechanisms by which Cit supplementation might be ergogenic.…”
Section: Discussioncontrasting
confidence: 99%
“…While L-citrulline malate supplementation has been shown to increase muscle force production (7,19), improve muscle contractile efficiency (19), and prevent the decline in muscle force production with endotoxemia (18), studies investigating the effects of Cit on exercise performance or muscle fatigue resistance are limited and equivocal. Of the two studies investigating the influence of Cit supplementation on exercise performance to date, one reported improved exercise tolerance in mice performing swimming exercise (56), while the other showed that Cit compromised incremental exercise performance in humans (26). It is unclear why our findings contrast with those of Hickner et al (26).…”
Section: Severe-intensity Exercisecontrasting
confidence: 58%
See 3 more Smart Citations